A maturity assessment model for data governance in small and medium enterprises in Vietnam - Hai, Chu Thi Hong (Edelweiss Applied Science and Technology, 2025)
Within digital transformation, data governance is vitally important for business performance improvement. However, small and medium-sized enterprises (SMEs) in Vietnam struggle to achieve this due to their resource and readiness levels, as well as their technological capabilities. The data maturity models that exist, such as DAMA-DMBOK and DCAM, face a similar problem as they are designed for larger enterprises and are not easily applicable to SMEs. This paper seeks to create a model that is more suitable for Vietnamese SMEs. To achieve this, the research is conducted through document analysis, interviewing 20 data governance professionals, and conducting test research within 20 target SMEs across the manufacturing, trade, and service industries. The outcomes reveal that the model assists SMEs in improving data literacy, developing data governance policies, fulfilling security compliance measures, and integrating cloud data systems. Respondents from SMEs claiming to possess the highest level of maturity, on average, reported a 20% relative increase in business performance. In addition to contributing to data governance theory, this model is the first framework that cost-effectively aids Vietnamese SMEs in complying with Decree 13/2023/ND-CP while simultaneously improving their competitive abilities.